Use of DWI in identification of small solid pancreatic focalities (≤ 2 cm) - Negri, Francesco; Bono, Nicola Emanuele; Barbalace, Sandro; Trunfio, Vincenzo; Lana, Silvia; Ganazzoli, Chiara; Marcantoni, Emanuela Angela; Totaro, Marilina; Vallara, Manuela; Parziale, Raffaele; Borgia, Daniele (Acta Biomedica Atenei Parmensis, 2016)
Incidental finding of pancreatic focalities has increased thanks to a larger use of radiological examinations (Ultrasound, CT). The differential diagnosis between focal inflammatory and heteroplastic disease is frequently complicated by the wide spectrum of lesions and by the aspecificity of clinical and medical history, as well as of imaging findings. MRI is the second level choice of examination thanks to its higher intrinsic contrast resolution and parametric capability (1); furthermore, the use of Diffusion Weighted Imaging (DWI) sequences provides additional diagnostic informations.